Study of the pattern and injury severity score of fatal blunt abdominal injuries sustained in road traffic accident - Deb Barman, Dipayan; Karnaboopathy , R (Journal of Indian Academy of Forensic Medicine, 2019)
Road traffic accident accounts for considerable morbidity and mortality all over the world. In this study out of the 98 cases of deaths  due to road traffic accidents which were subjected to medico-legal autopsy, 50 cases (51.02%) had blunt abdominal injuries and 48  cases had combined thoraco-abdominal and other injuries sustained as a result of road traffic accidents. Among the intra-abdominal  injuries in 34 (34.69%) cases laceration of the liver alone was responsible for the massive haemo-peritoneum, while in 28 (28.57%) of  the cases there was combined laceration of both liver and spleen. Kidney laceration was found in 20(20.41%) of the cases. The  commonest cause of death was found to be combined head injury and haemorrhagic shock (as a result of trauma leading to intraabdominal bleeding due to laceration of the liver and spleen) constituting 62 cases (63.27%), and this was followed by 18 (18.36%)  cases of death due to haemorrhagic shock. It was found that in victims of Road traffic accident (RTA) where Injury severity score (ISS)  was low (21-30 and 31-40 ISS score ranges) survival duration was more as compared to the victims who had high ISS (51-60, 61-70  and 71-75 ISSscore ranges) based on the severity of their injury.
Keywords: Road traffic accident; Thoraco-abdominal injuries; Autopsy